2001
DOI: 10.1590/s0104-11692001000300008
|View full text |Cite
|
Sign up to set email alerts
|

Adultos hipertensos hospitalizados: percepção de gravidade da doença e de qualidade de vida

Abstract: HOSPITALIZED HYPERTENSIVE ADULTS: PERCEPTIONS OF DISEASE GRAVITY AND OF LIFE QUALITYThe purpose of this descriptive study was to identify the perception of life quality in hospitalized hypertensive adults, confronting the data related to life quality with perceptions of disease gravity. The population comprised 83 patients hospitalized in the Medical Clinic of the University Hospital at the Federal University of Mato Grosso do Sul (UFMS). The data were collected by means of interviews using a health evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
19

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 10 publications
1
8
0
19
Order By: Relevance
“…Para avaliar a percepção da gravidade da doença, do tratamento e o tempo de tratamento da hipertensão, utilizou-se uma questão proposta por pesquisadores 7,8 , a qual oferece três opções diferentes de resposta: (i) curável com tratamento; (ii) a doença pode ser curada, mesmo sem tratamento; e (iii) não cura a doença, mas con- Análise e discussão dos resultados Dos 113 portadores de hipertensão arterial, a maioria era do sexo feminino (n = 87; 77%). O maior número de mulheres atendidas nos programas de hipertensão arterial é observado talvez em razão das características da mulher como cuidadora e mais atenta aos aspectos de sua saúde.…”
Section: Metodologiaunclassified
“…Para avaliar a percepção da gravidade da doença, do tratamento e o tempo de tratamento da hipertensão, utilizou-se uma questão proposta por pesquisadores 7,8 , a qual oferece três opções diferentes de resposta: (i) curável com tratamento; (ii) a doença pode ser curada, mesmo sem tratamento; e (iii) não cura a doença, mas con- Análise e discussão dos resultados Dos 113 portadores de hipertensão arterial, a maioria era do sexo feminino (n = 87; 77%). O maior número de mulheres atendidas nos programas de hipertensão arterial é observado talvez em razão das características da mulher como cuidadora e mais atenta aos aspectos de sua saúde.…”
Section: Metodologiaunclassified
“…Embora a hipertensão seja uma afecção crônica grave que se não tratada corretamente leva ao surgimento de complicações com comprometimento de órgãos importantes, na percepção do hipertenso sua doença não é grave, portanto, não necessitando de acompanhamento especializado (8) . (13) , ao descrever em seus resultados que a prevalência da hipertensão arterial aumenta progressivamente com o aumento da idade.…”
Section: Introductionunclassified
“…Besides the recognition and control of hypertension and its effects on morbidity and mortality, the evaluation of the health related quality of life (HRQoL) has been considered another important measure of outcome in treating hypertensive patients (4) . Studies have reported worse HRQoL among hypertensive individuals compared with those without hypertension (5) , which has been attributed to factors such as adverse effects related to the pharmacological therapy (6) , stigma associated with recognition by the subject of the hypertension -called the labeling effect (7) , as well as symptoms arising from diastolic heart failure (8) .…”
Section: Introductionmentioning
confidence: 99%